A Wearable Body Condition Sensor System with Wireless Feedback Alarm Functions. Issue 18 (26th March 2021) - Xu, Kaichen; Fujita, Yusuke; Lu, Yuyao; Honda, Satoko; Shiomi, Mao; Arie, Takayuki; Akita, Seiji; Takei, Kuniharu
Abstract: Emerging feedback systems based on tracking body conditions can save human lives. In particular, vulnerable populations such as disabled people, elderly, and infants often require special care. For example, the high global mortality of infants primarily owing to sudden infant death syndrome while sleeping makes request for extraordinary attentions in neonatal intensive care units or daily lives. Here, a versatile laser‐induced graphene (LIG)‐based integrated flexible sensor system, which can wirelessly monitor the sleeping postures, respiration rate, and diaper moisture with feedback alarm notifications, is reported. A tilt sensor based on confining a liquid metal droplet inside a cavity can track at least 18 slanting orientations. A rapid and scalable laser direct writing method realizes LIG patterning in both the in‐plane and out‐of‐plane configurations as well as the formation of nonstick conductive structures to the liquid metal. By rationally merging the LIG‐based tilt, strain, and humidity sensors on a thin flexible film, the multimodal sensor device is applied to a diaper as a real‐time feedback tracking system of the sleeping posture, respiration, and wetness toward secure and comfortable lives. User‐friendly interfaces, which incorporate alarming functions, provide timely feedback for caregivers tending to vulnerable populations with limited self‐care capabilities. Abstract : Vulnerable populations such as disabled people, elderly, and infants often require special care. A versatile laser‐induced graphene‐based integrated flexible sensor system is applied to a diaper as a real‐time feedback tracking system of sleeping posture, respiration, and wetness, toward secure and comfortable lives. The multifunctional wireless sensor system can especially save newborn infants' lives during sleep.